(untitled) (Revista Brasileira de Contabilidade e Gestão, 2018)
Since the implementation of the Public Digital Bookkeeping System - SPED in Brazil, several accounting and tax books began to be issued electronically, within a specific and standardized digital format. Therefore, the present study aims at verifying the financial and tax impacts, as well as verifying the necessary adjustments that an automotive industry will have to make to fit the Block K generation, within the EFD / Fiscal Sped. In terms of methodology, this is a case study, descriptive and qualitative. In this study, the necessary costs were evidenced, such as personnel training, software system adaptation and mainly internal process review, for greater inventory control, product structure and tax reclassification in accordance with legal regulations. It was also possible to demonstrate some tax impacts than with the delivery of the Block K file, which demands more and more responsibility with its fiscal writing. In addition, it became clear that with this new obligation, the company had a gain from the improvements and adjustments needed to improve internal controls.